Who counts as diverse? The strategic broadening and narrowing of diversity - Zhang, Junming; Kirby, Teri A. (Frontiers in Psychology, 2024)
A large majority of US organizations profess a commitment to diversity, but their definitions of diversity can vary greatly. While previous research demonstrates a shift in diversity definitions to include fewer protected demographic groups and more non-demographic characteristics, the present research examines whether this shift might be a motivated process among dominant group members related to anti-egalitarian and colorblind belief systems. White Americans (N = 498) were asked how they define diversity, as well as who should be included in a range of diversity initiatives. White participants’ higher anti-egalitarian belief was associated with stronger colorblind ideology endorsement, which was then associated with shifting their definition of diversity to include fewer disadvantaged demographic groups, more advantaged demographic groups, and non-demographic groups, as well as employing a colorblind inclusion rhetoric. Instead of only “broadening” diversity to include more characteristics than diversity’s original focus, White Americans higher in anti-egalitarian and colorblind motives exhibited a simultaneous “narrowing” of diversity to include fewer protected demographic characteristics. Taken together, these findings have implications for dominant group members’ definition of diversity and the subtle ways in which colorblind ideology may be enacted.